Laminated composite material toughening intermediate layer and preparation method thereof

By introducing a surface-treated aramid short fiber toughening intermediate layer into the CF/PEEK composite material, the problem of weak mechanical properties of the CF/PEEK composite material in the thickness direction is solved, interlayer toughening and interface compatibility are achieved, and the overall mechanical properties and service life of the material are improved.

CN120700696AActive Publication Date: 2025-09-26JILIN UNIVERSITY

Patent Information

Application Number
CN202511202717.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-27
Publication Date
2025-09-26
Estimated Expiration
2045-08-27

AI Technical Summary

Technical Problem

The existing CF/PEEK composite materials have weak mechanical properties in the thickness direction and are prone to delamination damage, which affects their overall mechanical properties and service life. There is currently a lack of effective interlayer toughening methods.

Method used

Aramid staple fibers were used as toughening materials. Active groups were generated by surface hydrofluoric acid etching, and soluble polyetheretherketone resin was grafted. After reduction treatment at high temperature, a crystalline polyetheretherketone grafted and impregnated aramid staple fiber toughening intermediate layer was prepared to achieve interface compatibility with CF/PEEK composite materials and interlayer toughening.

Benefits of technology

The interlaminar fracture toughness and anti-delamination ability of the CF/PEEK composite material are improved, ensuring the excellent compatibility of the toughening layer and the main composite resin matrix, avoiding the heterogeneous interface phenomenon, and achieving high-strength interface bonding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120700696A_ABST
    Figure CN120700696A_ABST
Patent Text Reader

Abstract

The invention is suitable for the technical field of composite materials, and provides a laminated composite material toughening intermediate layer and a preparation method thereof, and the preparation method comprises the following steps: obtaining an aramid short fiber wet-laid non-woven felt by using a processing method of a wet non-woven material; then the aramid fiber surface is activated through hydrofluoric acid etching; the preparation method comprises the following steps: grafting soluble polyether-ether-ketone resin with an active end group on the surface of the aramid fiber, and impregnating the aramid fiber at the same time; and the polyetheretherketone resin grafted on the surface of the aramid fiber is re-endowed with crystallinity through acidification reduction reaction of the polyetheretherketone resin grafted on the surface of the aramid fiber. According to the invention, the interface bonding performance of the aramid fiber toughening middle layer in the laminated composite material is regulated and controlled, the interlayer toughness of the carbon fiber reinforced polyether-ether-ketone composite material laminated board can be effectively improved while the original crystallinity of the polyether-ether-ketone resin is maintained, the possibility of interlayer cracking can be obviously reduced, a brand new scheme is provided for interlayer toughening of such materials, and the application prospect is broad. The material has potential application prospects in the fields of aerospace special materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite materials, and in particular relates to a toughening middle layer of a laminated composite material and a preparation method thereof. Background Art

[0002] High-performance fiber-reinforced polyetheretherketone (PEEK)-based composites hold great promise for applications in aerospace, healthcare, automotive, drones, and industrial products. Continuous carbon fiber-reinforced polyetheretherketone (CF / PEEK) composites are the strongest and most widely used composite materials. The excellent mechanical properties of carbon fibers endow laminated composites with exceptional in-plane mechanical properties. However, the carbon fiber layers rely solely on the polyetheretherketone (PEEK) resin to transfer load and energy, resulting in relatively weak mechanical properties through the thickness of the material. In practical applications, when laminates are subjected to external loads, internal failure occurs first in the weaker resin areas, making delamination highly likely. Delamination is one of the most common failure modes in composites. Once it occurs, the mechanical properties of the fibers cannot be fully utilized, which affects the overall mechanical performance and service life of the composite, limiting its application. Therefore, improving the interlaminar properties and delamination resistance of composites is crucial for the application and development of CF / PEEK composites.

[0003] Currently, methods for improving the interlaminar fracture toughness of composite materials primarily include resin toughening, Z-direction toughening, and interlaminar toughening. Interlaminar toughening achieves this toughness by adding toughening materials (such as films, particles, and fibers) between composite layers. This interlaminar toughening technique does not alter the existing composite molding process, is relatively easy to implement, and offers significant strengthening effects. The toughening layer bridges microcracks in the resin-rich region and deflects them, absorbing significant energy and thereby increasing the interlaminar fracture toughness of the composite. The thickness of the interlaminar film affects the overall thickness of the component, and thus the mechanical properties of the composite. The uniform distribution of interlaminar particles is difficult to control. However, interlaminar fibers, due to their high uniformity, large specific surface area, and minimal impact on the thickness of the composite, have become a research hotspot for interlaminar toughening. Furthermore, chopped fibers are readily available, have low processing costs, and can address the resource waste associated with the production of long fibers and composite materials, making them an ideal interlaminar toughening material. Therefore, research on interlaminar toughening of composite materials using chopped fibers is of great value.

[0004] The toughening properties of chopped aramid fibers not only offer fiber debonding, pullout, and transverse fracture resistance, but also unique longitudinal tear toughening. Previous studies have shown that chopped aramid fibers offer significantly better toughening than short fibers such as carbon fiber, glass fiber, and basalt fiber. However, most current research focuses on the interlaminar toughening of carbon fiber-reinforced epoxy resin composites (CF / EP) using chopped aramid fibers. Application of this technology to interlaminar toughening of CF / PEEK composites has not yet been reported in China. Therefore, the present invention proposes a toughening interlayer for laminated composites and a method for preparing the same. Summary of the Invention

[0005] The purpose of the present invention is to provide a toughening intermediate layer of a laminated composite material and a preparation method thereof, in order to solve the problems raised in the above background technology.

[0006] The purpose of the present invention is achieved through the following technical solutions: A method for preparing a toughened intermediate layer of a laminated composite material comprises the following steps: Step 1: Cut the aramid fiber into 5-6 mm pieces, put it into deionized water, and add a compound dispersant. By controlling the dispersant ratio, beating speed (500 r / min) and slurry solid content (representing "0.5-2.3 g of aramid fiber cut into 5-6 mm pieces is put into a beaker filled with 5L deionized water") and other parameters, ensure that the aramid fiber is fully dispersed in the dispersant solution; then, vacuum suction technology (using a large sand core funnel with a diameter of 18 mm for filtration) is used for collection and solid-liquid separation to obtain an aramid staple fiber wet-laid nonwoven felt; Step 2: By etching the aramid staple fiber wet-laid nonwoven felt with hydrofluoric acid, abundant -F groups are added to the surface of the aramid fiber as grafting sites for subsequent reactions; and obvious etching and peeling marks are produced on the surface of the aramid fiber after etching, making it relatively rough from a smooth surface, thereby increasing the physical anchoring effect between the resin and the aramid fiber; Step 3: Synthesizing a high-toughness ketimine biphenyl polyetheretherketone (PEEK) resin soluble in an organic solvent as an interface modification macromolecule and impregnation liquid for aramid staple fiber wet-laid nonwoven felt, specifically comprising: first synthesizing a polyetheretherketone polymer monomer containing a ketimine structure through a Schiff base reaction, then preparing a capping agent monomer with an amino terminal group through a Friedel-Crafts acylation reaction and a reduction reaction; then polymerizing the polymer monomer with biphenol, and adding a capping agent monomer with an amino terminal group in the later stage of the polymerization to cap the polymer to ensure the successful subsequent grafting reaction, thereby obtaining a soluble polyetheretherketone resin; Step 4: performing one-step interface modification on the aramid staple fiber wet-laid nonwoven felt to obtain a surface-modified aramid staple fiber toughened intermediate layer; Step 5: The polyetheretherketone resin in the aramid staple fiber felt is reduced to crystalline polyetheretherketone by acid reduction to obtain the target crystalline polyetheretherketone grafted and impregnated aramid staple fiber toughening intermediate layer, providing an intermediate layer with interlayer toughening effect for the subsequent high-temperature hot-pressing carbon fiber reinforced polyetheretherketone composite material.

[0007] Furthermore, the method specifically includes the following steps: Step 1: 0.5-2.3 g of aramid fiber chopped to 5-6 mm was put into a beaker containing 5 L of deionized water, and a compound dispersant was added: 0.03% (wt%) sodium dodecylbenzenesulfonate (SDS), 0.01% (wt%) anionic polyacrylamide (APAM) and 0.06% (wt%) polyethylene oxide (PEO). The mixture was stirred at a speed of 500 r / min for 120 min using a mechanical stirrer, and filtered using a large sand core funnel with a diameter of 18 mm to obtain a uniformly dispersed aramid staple fiber wet-laid nonwoven felt with an area density of 25-100 g / m 2 , drying at 100°C for 12h; Step 2: The dried aramid staple fiber wet-laid nonwoven felt was treated with a 10% (wt%) hydrofluoric acid solution. After continuous soaking for 30 minutes, the felt was washed with deionized water three times for 1 hour each time to ensure that the residual hydrofluoric acid was removed. The felt was then vacuum-dried at 100°C for 12 hours to obtain a fluorinated aramid staple fiber wet-laid nonwoven felt. Step 3: 1,1-bis(4-fluorophenyl)-N-phenylmethanimine with a ketimine structure generated by the reaction of aniline and 4,4'-difluorobenzophenone is used as a polymerization monomer to prevent the formation of a crystalline structure and make the polymer have good solubility. A soluble polyetheretherketone resin is prepared through a stepwise polymerization reaction and amino-terminated in the later stage of the reaction; Step 4: Weigh 0.5-2.3 g of soluble polyetheretherketone resin and dissolve it in 50 ml of tetrahydrofuran solution. Use all of it to impregnate and graft fluorinated aramid staple fiber wet-laid non-woven felt. Seal the system for 12 hours and shake it appropriately. After the grafting is complete, open the system. After the solvent is completely evaporated at room temperature, perform high-temperature hot pressing at 140°C and 10 MPa for 20 minutes to obtain a surface-modified aramid staple fiber toughening intermediate layer (i.e., a smooth and smooth grafted and impregnated amorphous polyetheretherketone aramid staple fiber toughening intermediate layer) with a surface density of 50-200 g / m 2 ; Step 5: Use a 1L capacity hydrothermal synthesis reactor liner, load 500mL of 1M hydrochloric acid solution for acidification reduction reaction, trim the surface-modified aramid staple fiber toughening intermediate layer prepared in step 4 to an appropriate size so that it can be completely immersed in the hydrochloric acid solution in the reactor, place the liner in the hydrothermal synthesis reactor, tighten the lid, heat at 150°C for 12h, take out the reduced aramid staple fiber toughening intermediate layer, wash it thoroughly with water, and vacuum dry it to obtain the target crystalline polyetheretherketone grafted and impregnated aramid staple fiber toughening intermediate layer.

[0008] Furthermore, the synthesis process of the soluble polyetheretherketone resin in step 3 comprises the following steps: Step 31: Synthesize a polymer monomer containing a ketimine structure, 1,1-bis(4-fluorophenyl)-N-phenylmethanimine, via a Schiff base reaction. Specifically, place toluene (80 mL), aniline (14 mL, 150 mmol), 4,4'-difluorobenzophenone (22.0 g, 100 mmol), and molecular sieves (4 Å, 50 g, activated at 400°C for 4 h) in a 250 mL three-necked flask. Heat the reaction system to reflux under a nitrogen atmosphere and react for 24 h. The molecular sieves are then filtered to remove the molecular sieves, and the toluene in the filtrate is evaporated to dryness to obtain a reddish-brown crude product. Due to the high purity requirements for the polymer monomer, the crude product is recrystallized three times from methanol to obtain light yellow block crystals with a yield of 62%. Step 32: 4-Fluoro-4'-nitrobenzophenone was synthesized by Friedel-Crafts acylation of fluorobenzene and 4-nitrobenzoyl chloride. The specific operation was as follows: first, fluorobenzene (80 mL) was added to a 250 mL three-necked flask, and then 4-nitrobenzoyl chloride (18.5 g, 100 mmol) was added thereto and stirred until completely dissolved; then, the three-necked flask was placed in an ice bath at 0°C, and anhydrous AlCl3 (17 g, 128 mmol) that had been ground in advance was slowly added (pay attention to keep the temperature low during the addition process), and after stirring at 0°C for 2 h, the mixture was heated. The reaction mixture was heated to reflux temperature and maintained for 6 hours. After the reaction was completed, the mixture was cooled to room temperature. 100 mL of deionized water was then slowly added to the three-necked flask, and the mixture was then heated to reflux temperature. Excess fluorobenzene was removed by a Dean-Stark water trap. After the fluorobenzene was completely removed, the reaction system was cooled to room temperature and the product was poured into cold water. A crude beige product was precipitated at the bottom. The crude beige product was filtered and washed three times with a sodium hydroxide solution (0.5 M) and deionized water. The crude product was dissolved in ethanol and recrystallized twice to obtain light yellow crystals of 4-fluoro-4'-nitrobenzophenone with a yield of approximately 85%. 4-Fluoro-4'-nitrobenzophenone was reduced to 4-fluoro-4'-aminobenzophenone using tin(II) chloride dihydrate. The specific operation was as follows: first, methanol (150 mL) and 4-fluoro-4'-nitrobenzophenone (0.012 mol, 2.94 g) were added to a 250 mL three-necked flask, and then tin(II) chloride dihydrate (0.06 mol, 13.48 g) was added to the three-necked flask; after reacting at reflux temperature for 6 hours, the insoluble matter was filtered off; the filtrate was evaporated and concentrated, and the pH value of the filtrate was adjusted to 9 with a saturated aqueous solution of Na2CO3 to remove excess tin salts; after filtration, the mixture was extracted twice with ethyl acetate, the organic phases were combined and dried over anhydrous sodium sulfate, the sodium sulfate was filtered off, and the organic phase was desolvated by rotary evaporation to obtain an orange product, which was dried in vacuo with a yield of approximately 68%; Step 33: Polymerization was carried out using 1,1-bis(4-fluorophenyl)-N-phenylmethanimine and biphenol at a ratio of ketone:phenol = 1:1.03; the specific operation was as follows: 1,1-bis(4-fluorophenyl)-N-phenylmethanimine (5.866 g, 20 mmol), biphenol (4.008 g, 22 mmol), sulfolane (23.51 mL), anhydrous potassium carbonate (3.648 g, 26.4 mmol) and toluene (11.755 mL) were added to a 250 mL three-necked flask in sequence; the system was first heated to 120 ° C and maintained for 3 h, and the water generated by the reaction was removed by toluene. The reaction was observed in the water separator. Turbidity is produced; the temperature is then raised to 190°C to initiate the polymerization reaction, and the viscosity of the polymer continues to increase as the reaction proceeds, forming a viscous dark yellow polymer solution after 12 hours; after the polymerization is completed, the heating power is reduced, the system is cooled to 130°C, 4-fluoro-4'-aminobenzophenone end-capping agent (0.901 g, 3 mmol) is added, and the reaction is continued at 120°C for 4 hours; the product is discharged in methanol to obtain amino-terminated strip polymers, which are crushed and washed three times with ethanol, water, and ethanol at reflux temperature; finally, the product is placed in a vacuum oven and dried for 12 hours to obtain an orange-yellow powdery soluble polyetheretherketone resin.

[0009] A toughened intermediate layer of a laminated composite material prepared according to the above-mentioned preparation method.

[0010] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention innovatively introduces a wet-laid nonwoven mat of aramid staple fibers, modified with a homologous resin interface, as a toughening interlayer between the CF / PEEK composite layers. This design, for the first time, combines the inherent toughness of aramid fibers with the high toughness and excellent compatibility of polyetheretherketone resin at the molecular and material structural levels. This innovative solution addresses the interface bonding challenge between the aramid interlayer and the CF / PEEK resin matrix, thereby achieving synergistic and efficient toughening between the composite layers.

[0011] 2. The key innovation of the present invention's toughening interlayer lies in the fact that both the resin used for grafting the aramid fiber surface and the resin used for impregnation throughout the layer are polyetheretherketone (PEEK), which is completely homologous to the matrix resin of the CF / PEEK composite prepreg tape. This "homologous" resin design fundamentally enables the grafting and impregnation of soluble polyetheretherketone onto the aramid fiber. Furthermore, subsequent reduction treatment restores the crystallinity of the polyetheretherketone, facilitating hot pressing. This design ensures excellent compatibility between the toughening layer and the main composite resin matrix, avoiding the formation of heterogeneous interfaces or phase separation, which are the foundation for achieving a high-strength interface.

[0012] 3. To address the challenge of aramid fiber's inert surface resisting good bonding with resin, this invention innovatively utilizes hydrofluoric acid treatment to fluorinate the aramid fiber surface. This treatment not only significantly alters the fiber's surface physical morphology but, more importantly, generates reactive groups in situ, providing the necessary reaction sites for subsequent precise interface chemistry control and a key step in achieving strong interfacial bonding.

[0013] 4. This invention successfully restores the inherent crystalline properties of soluble PEEK by subjecting the soluble PEEK resin layer grafted onto the aramid fiber surface to a specific reduction reaction, transforming the amorphous structure introduced for solubility into highly crystalline PEEK. This "interfacial crystallization" technology minimizes the risk of weak interfacial bonding caused by differences in resin state, thereby achieving high-strength interfacial fusion with the matrix resin. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 Schematic diagram of the preparation method of the present invention.

[0015] Figure 2 This is a scanning electron microscope photograph of the fluorinated aramid staple fiber wet-laid nonwoven felt in Example 1.

[0016] Figure 3 This is a photo of the crystalline polyetheretherketone grafted and impregnated aramid staple fiber toughened middle layer in Example 1.

[0017] Figure 4 This is a scanning electron microscope photograph of the surface of the crystalline polyetheretherketone grafted and impregnated aramid staple fiber toughened intermediate layer in Example 1.

[0018] Figure 5 This is the tensile stress-strain curve of the crystalline polyetheretherketone grafted and impregnated aramid staple fiber toughened intermediate layer in Example 1.

[0019] Figure 6 This is a differential scanning calorimeter (DSC) curve of the crystalline polyetheretherketone grafted and impregnated aramid staple fiber toughened middle layer in Example 1. DETAILED DESCRIPTION

[0020] In order to have a clearer understanding of the technical features, objectives and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be understood as limiting the scope of implementation of the present invention.

[0021] The specific implementation of the present invention is described in detail below with reference to specific embodiments. Example

[0022] This embodiment provides a method for preparing an aramid staple fiber intermediate layer having an interlayer toughening effect for a laminated composite material, and the specific steps are as follows: (1) 1.13 g of aramid fiber chopped to 6 mm was placed in a beaker containing 5 L of deionized water. A compound dispersant was added: 0.03% (wt%) sodium dodecylbenzenesulfonate (SDS), 0.01% (wt%) anionic polyacrylamide (APAM) and 0.06% (wt%) polyethylene oxide (PEO). A mechanical stirrer (Xiuniu Technology, JB80-SH) was used to stir at a speed of 500 r / min for 120 min. A large sand core funnel with a diameter of 18 mm was used for filtration to obtain a uniformly dispersed aramid staple fiber wet-laid nonwoven felt with an area density of 50 g / m 2 , dry at 100°C for 12h.

[0023] (2) The dried aramid staple fiber wet-laid nonwoven felt was treated with a 10% (wt%) hydrofluoric acid solution. After continuous immersion for 30 minutes, it was washed with deionized water three times, each time for 1 hour to ensure the removal of residual hydrofluoric acid. The felt was then vacuum-dried at 100°C for 12 hours to obtain a fluorinated aramid staple fiber wet-laid nonwoven felt. Figure 2 This is a scanning electron microscope image of a wet-laid nonwoven felt made of fluorinated aramid staple fibers. The image shows obvious etching and peeling marks on the surface of the aramid fibers, proving that the active -F groups have been successfully attached to the surface of the aramid fibers.

[0024] (3) The polyetheretherketone monomer 1,1-bis(4-fluorophenyl)-N-phenylmethaniline containing a ketimine structure was synthesized by Schiff base reaction. Toluene (80 mL), aniline (14 mL, 150 mmol), 4,4'-difluorobenzophenone (22.0 g, 100 mmol), and molecular sieves (4Å, 50 g, activated at 400 °C for 4 h) were placed in a 250 mL three-necked flask. The reaction system was heated to reflux under nitrogen and reacted for 24 h, and then the molecular sieves were filtered to remove the molecular sieves. The toluene in the filtrate was evaporated to dryness to obtain a reddish-brown crude product. Since the purity of the polymer monomer is relatively high, the crude product was recrystallized three times in methanol to obtain light yellow block crystals with a yield of 62%.

[0025] (4) 4-Fluoro-4'-nitrobenzophenone was synthesized by Friedel-crafts acylation of fluorobenzene and 4-nitrobenzoyl chloride. First, fluorobenzene (80 mL) was added to a 250 mL three-necked flask, followed by 4-nitrobenzoyl chloride (18.5 g, 100 mmol) and stirred until completely dissolved. The three-necked flask was then placed in an ice bath at 0°C and anhydrous AlCl3 (17 g, 128 mmol) that had been ground in advance was slowly added (pay attention to keep the temperature low during the addition process). After stirring at 0°C for 2 h, the mixture was heated to reflux temperature and maintained for 6 h. After the reaction was completed, it was cooled to room temperature. Then, 100 mL of deionized water was slowly added to the three-necked flask. The mixture was then heated to reflux temperature and the excess fluorobenzene was removed by a Dean-Stark water trap. After the fluorobenzene was completely removed, the reaction system was cooled to room temperature and the product was poured into cold water. The crude beige product precipitated at the bottom. The beige crude product was filtered and washed three times with 0.5 M sodium hydroxide solution and three times with deionized water. The crude product was dissolved in ethanol and recrystallized twice to obtain pale yellow crystals of 4-fluoro-4'-nitrobenzophenone with a yield of approximately 85%.

[0026] 4-Fluoro-4'-nitrobenzophenone was reduced to 4-fluoro-4'-aminobenzophenone using tin(II) chloride dihydrate. Methanol (150 mL) and 4-fluoro-4'-nitrobenzophenone (0.012 mol, 2.94 g) were placed in a 250 mL three-necked flask, followed by the addition of tin(II) chloride dihydrate (0.06 mol, 13.48 g). After 6 h of reaction at reflux, the insoluble matter was filtered off. The filtrate was concentrated by evaporation, and the pH was adjusted to 9 with a saturated aqueous solution of Na2CO3 to remove excess tin salts. After filtration, the mixture was extracted twice with ethyl acetate. The combined organic phases were dried over anhydrous sodium sulfate. After filtering and removing the sodium sulfate, the organic phase was freed from the solvent on a rotary evaporator to yield an orange product, which was then dried in vacuo in a yield of approximately 68%.

[0027] (5) Polymerization was carried out using 1,1-bis(4-fluorophenyl)-N-phenylmethanamine and biphenol in a ratio of ketone:phenol = 1:1.03. 1,1-bis(4-fluorophenyl)-N-phenylmethanamine (5.866 g, 20 mmol), biphenol (4.008 g, 22 mmol), sulfolane (23.51 mL), anhydrous potassium carbonate (3.648 g, 26.4 mmol), and toluene (11.755 mL) were added to a 250 mL three-necked flask in sequence. The system was first heated to 120 °C and maintained for 3 h. Toluene was used to remove the water generated by the reaction. Turbidity was observed in the Dean-Stark water separator. The temperature was then raised to 190 °C to initiate the polymerization reaction. The viscosity of the polymer continued to increase, and a viscous dark yellow polymer solution was formed after 12 h. After the polymerization was complete, the heating power was reduced, the system was cooled to 130°C, and 4-fluoro-4'-aminobenzophenone (0.901 g, 3 mmol) was added as a capping agent. The reaction was continued at 120°C for 4 hours. The product was discharged into methanol to obtain amino-terminated polymer strips. The strips were then pulverized and washed three times each with ethanol, water, and ethanol at reflux temperature. Finally, the product was dried in a vacuum oven for 12 hours to obtain an orange-yellow powder of soluble polyetheretherketone resin.

[0028] (6) Weigh 1.13 g of soluble polyetheretherketone resin and dissolve it in 50 ml of tetrahydrofuran solution. Use the whole of it to impregnate and graft the fluorinated aramid staple fiber wet-laid nonwoven felt. Seal the system for 12 h and shake it appropriately. After the grafting is complete, open the system and wait for the solvent to evaporate completely at room temperature. Then, perform high-temperature hot pressing at 140°C and 10 MPa for 20 min to obtain a surface-modified aramid staple fiber toughened intermediate layer.

[0029] (7) A 1L hydrothermal synthesis reactor liner was used, and 500mL of 1M hydrochloric acid solution was loaded for acidification reduction reaction. The surface-modified aramid short fiber toughening intermediate layer prepared above was trimmed to a suitable size so that it could be completely immersed in the hydrochloric acid solution in the reactor. The liner was placed in the hydrothermal synthesis reactor, the lid was tightened, and the reactor was heated at 150°C for 12h. The reduced composite toughening intermediate layer was taken out, and after sufficient water washing and vacuum drying, the target crystalline polyetheretherketone grafted and impregnated aramid short fiber toughening intermediate layer (i.e., the interface-modified aramid short fiber toughening intermediate layer) was obtained, with a final surface density of about 100g / m 2 . Figure 3 This is a photo of the actual object. It can be seen that its surface is uniform and there are no obvious cloud spots or holes. Figure 4 A scanning electron microscope photo of its surface shows that the aramid fibers are randomly distributed and evenly coated with resin. Figure 5The stress-strain curve read after the tensile performance test shows that the stress increases linearly in the initial stage of stretching, and the maximum breaking stress is close to 15MPa, proving that the intermediate layer has good mechanical properties. Figure 6 The DSC test results show that during the heating process, the exothermic peak in the mid-temperature range (around 250-350°C) corresponds to the crystallization heat release caused by the regular arrangement of the PEEK molecular chains. The endothermic peak in the high-temperature range (around 350-450°C) (directed opposite to the EXO (exothermic)) represents the melting of the crystalline PEEK. This indicates that after acid reduction, the soluble PEEK modified on the surface of the aramid staple fiber-reinforced interlayer has lost its ketimine structure, resulting in the reappearance of the crystallization exothermic peak and the melting endothermic peak, demonstrating the restoration of its crystallization ability. This indicates that the soluble PEEK modified on the surface of the aramid staple fiber-reinforced interlayer can regain its crystallization properties. Example

[0030] This embodiment provides a method for preparing an aramid short fiber intermediate layer having a toughening effect between layers of a laminated composite material. The difference between this method and embodiment 1 is that the weight of the aramid fiber in step (1) is changed to 0.56 g, and the surface density of the uniformly dispersed aramid short fiber web obtained is 25 g / m 2 The weight of the polyetheretherketone resin in step (6) was also changed to 0.56g to obtain the target crystalline polyetheretherketone grafted and impregnated aramid short fiber toughening intermediate layer, with a final surface density of about 50g / m 2 . Example

[0031] This embodiment provides a method for preparing an aramid short fiber intermediate layer having a toughening effect between layers of a laminated composite material. The difference between this method and embodiment 1 is that the weight of the aramid fiber in step (1) is changed to 2.26 g, and the surface density of the uniformly dispersed aramid short fiber web obtained is 100 g / m 2 The weight of the polyetheretherketone resin in step (6) was also changed to 2.26g to obtain the target crystalline polyetheretherketone grafted and impregnated aramid short fiber toughening intermediate layer, with a final surface density of about 200g / m 2 . Example

[0032] The resin-fiber ratio of the intermediate layers provided in Examples 1 to 3 is 1:1. In order to prepare intermediate layers with different resin-fiber ratios, this Example provides a method for preparing an aramid short fiber intermediate layer with interlayer toughening effect of a laminated composite material. The difference between this method and Example 1 is that the weight of the aramid fiber in step (1) is changed to 1.13g, and the surface density of the uniformly dispersed aramid short fiber web obtained is 50g / m 2The weight of the polyetheretherketone resin in step (6) was changed to 2.26g to obtain the target crystalline polyetheretherketone grafted and impregnated aramid short fiber toughening intermediate layer, with a final surface density of about 150g / m 2 Soluble polyetheretherketone resin: aramid fiber (wt%) = 2:1. Example

[0033] This embodiment provides a method for preparing an aramid short fiber intermediate layer having a toughening effect between layers of a laminated composite material. The difference between this method and embodiment 1 is that the weight of the aramid fiber in step (1) is changed to 0.56 g, and the surface density of the uniformly dispersed aramid short fiber web obtained is 25 g / m 2 The weight of the polyetheretherketone resin in step (6) was changed to 1.12g to obtain the target crystalline polyetheretherketone grafted and impregnated aramid short fiber toughening intermediate layer, with a final surface density of about 75g / m 2 Soluble polyetheretherketone resin: aramid fiber (wt%) = 2:1.

[0034] In Examples 2-5, by adjusting the ratio of aramid fiber to soluble polyetheretherketone resin, crystalline polyetheretherketone grafted and impregnated aramid staple fiber toughening interlayers with varying surface densities were prepared. The resulting toughening interlayers exhibited stable performance and uniform fiber dispersion. The results demonstrate that the toughening interlayers prepared by the present invention exhibit excellent designability, enabling precise control of surface density by adjusting the resin / fiber ratio. This provides a foundation for studying the effects of varying structural parameters on the interlayer toughening effect of laminated composites and a basis for selecting the optimal ratio for practical applications.

[0035] The above are only preferred embodiments of the present invention. It should be pointed out that for those skilled in the art, several variations and improvements can be made without departing from the concept of the present invention. These should also be regarded as the scope of protection of the present invention. These will not affect the effect of the implementation of the present invention and the practicality of the patent.

Claims

1. A method for preparing a toughened intermediate layer of a laminated composite material, characterized in that: The following steps are involved: Step 1: Cut the aramid fiber into 5-6 mm pieces, put it into deionized water, add a compound dispersant, and ensure that the aramid fiber is fully dispersed in the dispersant solution by controlling the dispersant ratio, beating speed and slurry solid content parameters; then use vacuum suction technology to collect and separate the solid and liquid to obtain an aramid staple fiber wet-laid nonwoven felt; Step 2: By etching the aramid staple fiber wet-laid nonwoven felt with hydrofluoric acid, abundant -F groups are added to the surface of the aramid fiber as grafting sites for subsequent reactions; and obvious etching and peeling marks are produced on the surface of the aramid fiber after etching, making it relatively rough from a smooth surface, thereby increasing the physical anchoring effect between the resin and the aramid fiber; Step 3: Synthesizing a ketimine biphenyl polyetheretherketone resin soluble in an organic solvent as an interface modification macromolecule and impregnation liquid for the wet-laid nonwoven felt of aramid staple fibers, specifically comprising: first synthesizing a polyetheretherketone polymer monomer containing a ketimine structure through a Schiff base reaction; then preparing a capping agent monomer having an amino terminal group through a Friedel-Crafts acylation reaction and a reduction reaction; then polymerizing the polymer monomer with biphenol, and adding a capping agent monomer having an amino terminal group in the later stage of the polymerization to cap the polymer to obtain a soluble polyetheretherketone resin; Step 4: performing one-step interface modification on the aramid staple fiber wet-laid nonwoven felt to obtain a surface-modified aramid staple fiber toughened intermediate layer; Step 5: The polyetheretherketone resin in the aramid staple fiber felt is reduced to crystalline polyetheretherketone by acid reduction to obtain the target crystalline polyetheretherketone grafted and impregnated aramid staple fiber toughening intermediate layer.

2. The preparation method according to claim 1, characterized in that The specific steps include: Step 1: Put 0.5-2.3g of aramid fiber chopped to 5-6mm into a beaker filled with 5L of deionized water, add a compound dispersant: 0.03wt% sodium dodecylbenzene sulfonate, 0.01wt% anionic polyacrylamide and 0.06wt% polyethylene oxide, use a mechanical stirrer to stir at a speed of 500r / min for 120min, and use a large sand core funnel with a diameter of 18mm to filter to obtain a uniformly dispersed aramid staple fiber wet-laid nonwoven felt with an area density of 25-100g / m 2 , drying at 100°C for 12h; Step 2: The dried aramid staple fiber wet-laid nonwoven felt was treated with a 10 wt % hydrofluoric acid solution, and the treated felt was soaked for 30 minutes, washed with deionized water three times for 1 hour each time, and dried under vacuum at 100° C. for 12 hours to obtain a fluorinated aramid staple fiber wet-laid nonwoven felt; Step 3: Using 1,1-bis(4-fluorophenyl)-N-phenylmethanimine with a ketimine structure generated by the reaction of aniline and 4,4'-difluorobenzophenone as a polymerization monomer to prevent the formation of a crystalline structure, and preparing a soluble polyetheretherketone resin through a stepwise polymerization reaction and amino-terminated in the late stage of the reaction; Step 4: Weigh 0.5-2.3g of soluble polyetheretherketone resin, dissolve it in 50ml of tetrahydrofuran solution, impregnate and graft the fluorinated aramid staple fiber wet-laid non-woven felt, seal the system for 12h and shake it appropriately, open the system after the grafting is complete, wait for the solvent to evaporate completely at room temperature, and then perform high-temperature hot pressing at 140°C and 10MPa for 20min to obtain a surface-modified aramid staple fiber toughened intermediate layer with a surface density of 50-200g / m 2 ; Step 5: Use a 1L capacity hydrothermal synthesis reactor liner, load 500mL of 1M hydrochloric acid solution for acidification-reduction reaction, trim the surface-modified aramid staple fiber toughening intermediate layer so that it is completely immersed in the hydrochloric acid solution in the reactor, place the liner in the hydrothermal synthesis reactor, tighten the lid, heat at 150°C for 12h, take out the reduced aramid staple fiber toughening intermediate layer, wash it with water, and vacuum dry it to obtain the target crystalline polyetheretherketone grafted and impregnated aramid staple fiber toughening intermediate layer.

3. The preparation method according to claim 2, characterized in that The synthesis process of the soluble polyetheretherketone resin in step 3 comprises the following steps: Step 31: Synthesize a polymer monomer containing a ketimine structure, 1,1-bis(4-fluorophenyl)-N-phenylmethanimine, by a Schiff base reaction. Specifically, place 80 mL of toluene, 14 mL of aniline, 22.0 g of 4,4'-difluorobenzophenone, and 50 g of 4Å molecular sieves in a 250 mL three-necked flask; heat the reaction system to reflux under a nitrogen atmosphere and react for 24 hours, then filter to remove the molecular sieves, and evaporate the toluene in the filtrate to dryness to obtain a reddish-brown crude product; the crude product is recrystallized three times from methanol to obtain light yellow block crystals; Step 32: Synthesis of 4-fluoro-4'-nitrobenzophenone by Friedel-crafts acylation of fluorobenzene and 4-nitrobenzoyl chloride; the specific operation is as follows: first, add 80 mL of fluorobenzene to a 250 mL three-necked flask, then add 18.5 g of 4-nitrobenzoyl chloride, stirred until completely dissolved; placed the three-necked flask in a 0°C ice bath, slowly added 17g of pre-ground anhydrous AlCl3, stirred at 0°C for 2h, heated the mixture to reflux temperature and maintained for 6h, and cooled to room temperature after the reaction; then slowly added 100mL of deionized water to the three-necked flask, then heated to reflux temperature, and removed excess fluorobenzene through a Dean-Stark water trap; after fluorobenzene was completely removed, cooled the reaction system to room temperature, poured the product into cold water, and precipitated a blocky beige crude product, which was filtered and washed three times with 0.5M sodium hydroxide solution and deionized water; the crude product was dissolved in ethanol and recrystallized twice to obtain light yellow crystals of 4-fluoro-4'-nitrobenzophenone; 4-Fluoro-4'-nitrobenzophenone was reduced to 4-fluoro-4'-aminobenzophenone using tin(II) chloride dihydrate. The specific operation was as follows: first, 150 mL of methanol and 2.94 g of 4-fluoro-4'-nitrobenzophenone were added to a 250 mL three-necked flask, and then 13.48 g of tin(II) chloride dihydrate was added to the three-necked flask; after reacting at reflux temperature for 6 hours, the insoluble matter was filtered off; the filtrate was evaporated and concentrated, and the pH value of the filtrate was adjusted to 9 with a saturated aqueous solution of Na2CO3 to remove excess tin salts; after filtering, the mixture was extracted twice with ethyl acetate, the organic phases were combined and dried over anhydrous sodium sulfate, and after filtering out the sodium sulfate, the organic phase was desolvated by a rotary evaporator to obtain an orange product, which was then dried in vacuo; Step 33: Use 1,1-bis(4-fluorophenyl)-N-phenylmethamine and biphenyldiphenol to polymerize in a ratio of ketone:phenol = 1:1.03; the specific operation is as follows: 5.866g 1,1-bis(4-fluorophenyl)-N-phenylmethamine, 4.008g biphenyldiphenol, 23.51mL sulfolane, 3.648g anhydrous potassium carbonate and 11.755mL toluene are added in sequence to a 250mL three-necked flask; first, the system is heated to 120°C and maintained for 3h, and the water generated by the reaction is removed by toluene. Turbidity is observed in the water separator; then the temperature is raised to 190°C to start the polymerization reaction. As the reaction proceeds, the viscosity of the polymer continues to increase, and a viscous dark yellow polymer solution is formed after 12h; after the polymerization is completed, the heating power is reduced, the system is cooled to 130°C, and 0.901g 4-Fluoro-4'-aminobenzophenone end-capping agent was added, and the reaction was continued at 120°C for 4 hours. The product was discharged into methanol to obtain amino-terminated strip polymers. The strip polymers were crushed and washed three times with ethanol, water, and ethanol at reflux temperature. Finally, they were dried in a vacuum oven for 12 hours to obtain an orange-yellow powder of soluble polyetheretherketone resin.

4. A toughened intermediate layer of a laminated composite material prepared according to the preparation method according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Method for performing surface modification on reinforcing fiber by using crystalline polyaryletherketone sizing agent

    CN110924162A

  • Amino-terminated soluble polyaryletherketone, and preparation method and application thereof

    CN113105620A

  • Recovery method of fiber-reinforced polyaryletherketone resin-based composite material

    CN118290816A

  • Crystalline polyaryletherketone surface grafted carbon fiber and preparation method thereof

    CN119591939A

Cited By

  • Aramid interlayer toughening composite material added with carbon nanotubes and preparation method of aramid interlayer toughening composite material

    CN121552789A

  • A toughened composite material with an aramid interlayer reinforced by carbon nanotubes and its preparation method

    CN121552789B